"I'll do this no matter if I have to fight the world!". Issue 3 (10th August 2015) - Glenn Hardaker, Prof. Carol Evans, Professor; Bamford, Jan; Djebbour, Yaz; Pollard, Lucie
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of the paper was to explore students' learning experiences in culturally diverse urban higher education environments. Design/methodology/approach – The project used an action research method approach with a mixed-method collection of data. The data consist of a survey of undergraduate students from the two different faculties, business and science, in two London institutions (n = 393) and ten focus groups (consisting of 92 students) as well as participant observations. The survey was based on an adapted version of the National Survey on Student Engagement (NSSE) developed in the USA. The authors also piloted the use of Facebook as a learning tool and monitored the effects on communication between students and between lecturers. Findings – The authors identified statistical significance in the items that addressed the development of students' relationships with others and found that there was a link with specific students' profiles, that is those students who were non-native speakers of English who were less likely to engage with "others" and the learning environment. Focus groups highlighted the importance of communities of practice and that these communities aided students in developing what can be seen as resilience outcomes. Originality/value – The findings from the research indicated that resilience can be seen as key to increasing engagement and communication for students. The piloting of social media across a module at each research site indicated that such a tool can be useful in addressing issues of communication, but the introduction of such tools needs to be generated through the students.